35 let pozneje - Slaček Brlek, Aleksander Sašo (Javnost (Ljubljana), 2015)
The aim of this article is to situate the report of the International Commission for the Study of Communication Problems Many Voices, One World (more commonly known as the MacBride report) within its historic, social, political-economic and intellectual context. The report is regarded as one of the seminal interventions in the fi eld of international communication, and aimed to reduce inequalities in the access to means of communication between countries as well as within them. The article argues that critical thought and its practical application are necessarily conditioned by the wider social context. This is evident in the case of the MacBride report as well as in the development of political economy of communication, which formed the basis of the call for a New World Information and Communication Order and of its most important document, the MacBride report.
Keywords: komuniciranje; mednarodni odnosi; množično komuniciranje